Synthesis, characterization and thermal studies on solid state 3-methoxybenzoate of lighter trivalent lanthanides - Dametto, Patrícia Roberta; de Siqueira, Adriano Buzutti; de Carvalho, Cláudio Teodoro; Ionashiro, Massao (Eclética Química, 2007)
Solid-state Ln -3-MeO-Bz compounds, where Ln stands for lighter trivalent lanthanides (La – Sm) and 3-methoxybenzoate, have been synthesized. Thermogravimetry (TG), differential scanning calorimetry (DSC), X-ray powder diffractometry, infrared spectroscopy, and complexometry were used to characterize and to study the thermal behaviour of these compounds. The results led to information concerning the composition, dehydration, polymorphic transformation, thermal behaviour and thermal decomposition of the synthesized compounds.